2020
DOI: 10.1021/acs.langmuir.0c02696
|View full text |Cite
|
Sign up to set email alerts
|

Toehold-Mediated Selective Assembly of Compact Discrete DNA Nanostructures

Abstract: Production of small discrete DNA nanostructures containing covalent junctions requires reliable methods for the synthesis and assembly of branched oligodeoxynucleotide (ODN) conjugates. This study reports an approach for self-assembly of hard-to-obtain primitive discrete DNA nanostructures“nanoethylenes”, dimers formed by double-stranded oligonucleotides using V-shaped furcate blocks. We scaled up the synthesis of V-shaped oligonucleotide conjugates using pentaerythritol-based diazide and alkyne-modified olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“… 1–20 Bimolecular V-shape complexes and complexes of other molecularity can be created by means of various non-nucleotide linkers of different lengths, rigidity levels, charges, and hydrophobicity values. 21,23 Moreover, potentially, triplex formation by linkers, non-canonical base pairing, duplex blocks' interactions (for example, similar to those reported for DNA crossovers 61 ), introduction of a chemical modification into oligonucleotides, the formation of catenanes, 62 and other DNA structural factors could affect the efficiency of the self-association of DNA oligomers' and complexes' types formed at thermodynamic equilibrium. In addition, cations significantly stabilize self-limited complexes by shielding electrostatic repulsion and/or via coordination of phosphate residues.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“… 1–20 Bimolecular V-shape complexes and complexes of other molecularity can be created by means of various non-nucleotide linkers of different lengths, rigidity levels, charges, and hydrophobicity values. 21,23 Moreover, potentially, triplex formation by linkers, non-canonical base pairing, duplex blocks' interactions (for example, similar to those reported for DNA crossovers 61 ), introduction of a chemical modification into oligonucleotides, the formation of catenanes, 62 and other DNA structural factors could affect the efficiency of the self-association of DNA oligomers' and complexes' types formed at thermodynamic equilibrium. In addition, cations significantly stabilize self-limited complexes by shielding electrostatic repulsion and/or via coordination of phosphate residues.…”
Section: Discussionmentioning
confidence: 77%
“…Self-limited complexes of various molecularity levels can be obtained by varying duplex block length, linker length, and nucleotide content and terminal nucleotides in the duplex blocks and by bending the duplex block. 21,22,28,33,34 Efficient assembly of a self-limited complex can be realized if lengths of the blocks are the same. For example, we found that oligonucleotides with duplex-forming blocks of 20 nt can give rise to self-limited complexes without any linkers (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations